Judging Strangers’ Trustworthiness is Associated with Theory of Mind Skills - Prevost, Marie; Brodeur, Mathieu; Onishi, Kristine H.; Lepage, Martin; Gold, Ian (Frontiers in Psychiatry, 2015)
Trusting people requires evaluating them to assess their trustworthiness. Evaluating a stranger’s intentions is likely to be one method of assessing trustworthiness. The present study tested the hypothesis that judgments of trustworthiness are associated with mindreading skills, also called theory of mind (ToM). We tested a group of healthy participants and a group of patients with paranoid schizophrenia. Both groups made theory of mind judgments and judged the trustworthiness of strangers. Participants were also assessed for their disposition to trust as well as levels of paranoid belief. As anticipated, healthy participants had normal ToM scores and patients with paranoid schizophrenia had poor ToM scores. In paranoid patients, better ability to read others' minds tended to be associated with judging others as more trustworthy, while the reverse was found in the healthy participants (better mind reading was associated with judging others as less trustworthy), suggesting a non-linear relationship between trust in others and being able to read their intentions.